Evaluation of high volume extracapsular cataract extraction with posterior chamber lens implantation in Sierra Leone, west Africa. Issue 8 (August 1996) - Cook, N J
Abstract : AIMS: Intraocular lens (IOP) implantation in sub-Saharan Africa is not the routine procedure of choice in the treatment of cataract. Previous series consist of small numbers of selected patients. The purpose of this study was to evaluate routine posterior chamber lens implantation in large numbers of consecutive patients. METHODS: 1059 cataract extractions with planned IOL (744 patients) were performed over a 1 year period from August 1993 to July 1994. RESULTS: 94.6% (1002) of eyes showed an improvement in visual acuity. A postoperative uncorrected acuity of 6/18 or better was attained in 41.7% of eyes, while 27.1% attained an uncorrected acuity of < 6/18 to 6/60. The commonest operative complication was posterior capsule rupture (11.4%). CONCLUSION: Extracapsular cataract extraction with posterior chamber lens implantation, performed in a well equipped clinic, can give satisfactory results in a developing country. Uncorrected visual acuity can be taken as an acceptable endpoint in the majority of cases.